2013
DOI: 10.4161/cc.27410
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of RBBP7 unveils a requirement of histone deacetylation for CPC function in mouse oocytes

Abstract: During mouse oocyte maturation histones are deacetylated, and inhibiting this deacetylation leads to abnormal chromosome segregation and aneuploidy. RBBP7 is a component of several different complexes that contain histone deacetylases, and therefore could be implicated in histone deacetylation. We find that Rbbp7 is a dormant maternal mRNA that is recruited for translation during oocyte maturation to regulate the histone deacetylation. Importantly, we show that the maturation-associated decrease of histone ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 48 publications
1
36
0
Order By: Relevance
“…Perturbing RBBP7 function phenocopies oocytes treated with trichostatin A (TSA), a global inhibitor of HDACs. These phenotypes include chromosome misalignment, cytokinesis defects, and aneuploidy at metaphase (Met) II [7]. Furthermore, we found that the changes in histone acetylation caused delocalization of the chromosomal passenger complex (CPC), which is consistent with the observed phenotypes.…”
Section: Introductionsupporting
confidence: 73%
See 2 more Smart Citations
“…Perturbing RBBP7 function phenocopies oocytes treated with trichostatin A (TSA), a global inhibitor of HDACs. These phenotypes include chromosome misalignment, cytokinesis defects, and aneuploidy at metaphase (Met) II [7]. Furthermore, we found that the changes in histone acetylation caused delocalization of the chromosomal passenger complex (CPC), which is consistent with the observed phenotypes.…”
Section: Introductionsupporting
confidence: 73%
“…The DNA linearization and purification were carried out as described previously [7,15]. In vitro transcription to generate Aurka-Gfp, Aurkc-Gfp, and H2b-mCherry was carried out using the mMessage mMachine T7 Ultra Kit (Ambion).…”
Section: In Vitro Crna Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Knockdown of retinoblastoma binding protein P46 (RBAP46, also called RBBP7), an integral subunit in HDAC1/2-containing complexes, results in similar phenotypes including H4K16 hyperacetylation and missegregation of chromosomes to that observed in Hdac2 mutant eggs. 76 Immunoblot analysis revealed that RBBP7 protein level increases significantly from GV to MII eggs; 76 this maturation-associated increase in RBBP7 protein is well correlated with activation of HDAC2. In addition, RBBP7 colocalizes with chromosomes during meiosis division, 76 suggesting that it may promote HDAC2 association with chromatin and thereby facilitate deacetylation of H4K16.…”
Section: Hdac2 Regulates Chromosome Segregation and Kinetochore Functmentioning
confidence: 88%
“…76 Immunoblot analysis revealed that RBBP7 protein level increases significantly from GV to MII eggs; 76 this maturation-associated increase in RBBP7 protein is well correlated with activation of HDAC2. In addition, RBBP7 colocalizes with chromosomes during meiosis division, 76 suggesting that it may promote HDAC2 association with chromatin and thereby facilitate deacetylation of H4K16.…”
Section: Hdac2 Regulates Chromosome Segregation and Kinetochore Functmentioning
confidence: 88%